Nursing care from the ethics of care and of gender. - Burgos, Cecilia Beatriz (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> Objective. To explore the ethical dimensions of the concept and application of care from a gender perspective, in female and male nurses from a public hospital in the southern zone of Chile. Methodology. Qualitative research was conducted using the case study methodology. Semi-structured interviews were made, between December 2011 and January 2012, of 11 nursing professionals (six women and five men) belonging to Hospital Base in the city of Valdivia, Chile. The data obtained and transcribed were read and coded to establish categories of meaning. Thematic analysis was performed from the statements. Results. A marked service vocation and motivation was observed to apply care, both in men as in women, emphasizing on the psychosocial sphere of patients. Additionally, commitment and application of values were verified in the care giving practice, recognized as part of the excellence of the nursing professional, which they perceive as a characteristic aspect of the profession. Conclusion. Nursing care is not exclusive of the female sex. Males and females develop an ethical sense of care closely linked to the vocational aspects. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->